Qiyas sebagai Konstitusi Keempat dalam Islam: Implementasi Qiyas dalam Konteks Siyasah - Ramadhan Siddik Pane; Sawaluddin Siregar (IAIN Padangsidimpuan, 2022)
Abstract The problem faced by Muslims today in a constitutional context is a complex one. A revolutionary solution is needed to answer the problem and it is certainly not enough to use the classical Islamic legal methods. When viewed in the Islamic constitution, many of the problems that arise today are textually absent from the provisions of the law. Thus, to answer these problems requires a systematic methodology and legal formulation. In answering and formulating legal provisions in contemporary cases, it can be done by the qiyas method. This study aims to formulate the qiyas methodology as the fourth constitution in Islam to answer all problems of Muslims in the context of siyasah. Various things that are the object of research are in the fields of siyasah harbiyah, siyasah dusturiyah, and siyasah maliyah. The three siyasah in the national constitutional system are known as the state defense system, the state legislative system, and the state revenue and taxation system. To facilitate this research, the author utilizes the theory of literature research with a qualitative research approach. Researchers first formulate one problem and then collect various literature models related to the theme. Then the researcher analyzes each of these literatures to formulate qiyas formulations in the context of siyasah. The main problem in this study is how the formulation of qiyas in formulating Islamic law and how to implement qiyas in the issue of siyasah. Therefore, the results of this study can be described as showing that the formulation of qiyas must meet four pillars, namely the initial case, the initial case law, the branch case, and the 'illat law between the two cases. Then qiyas can be implemented in answering problems in the field of siyasah harbiyah, siyasah dusturiyah, and siyasah maliyah Keywords: Constitution, Qiyas, Siyasah